TRANSPARANSI MUTASI PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN HALMAHERA UTARA - TAWARIS, MARIO; kALANGI, JHONNY; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2018)
This study moved from the initial observation that the process of implementation anddetermination of mutations of civil servants in the local government of North Halmahera Regency is lesstransparent. Thus, the research in addition to answering the problems related to transparency of civilservant mutations, also aims to know the application of the principle of transparency in the implementationof employee mutations at the Regional Personnel Agency (BKD) of North Halmahera Regency. Thisresearch applies descriptive method with qualitative approach, informant is determined based on level ofunderstanding to research problem as many as 12 people consisting of element BKD, some related SKPD,Member DPRD related commission and press. Methods of data collection consist of observation,documentation and interview. Processing and data analysis is done from the collection stage to the dataverifikasi stage by applying interactive techniques.The results showed that (1). Information relating to the process of formulating and implementing publicpolicies, including information on civil servant mutations, is sufficient, accessible, accessible and timely,but information is categorized as "confidential", including information on the process and determinationof civil servants to be transferred. (2). Transparency of information may increase the knowledge and insightof the community about the process, procedures, requirements and reasons for the transfer of civil servants,there are several considerations of civil servant’s mutation among others is the need for civil servants to fillvacant places / positions. Given the transparency of civil servant transfers, at least a slight increase in publicconfidence in the government. The level of public trust to the government due to the increased satisfactionis significant.Thus it can be concluded that the existence of transparency of information in terms of civil servant’smutations also affect the increased knowledge, insight, trust and community participation in regionaldevelopment. Participation in question has to do with reports for civil servants need to be transferred(critical Participation) to provide information to the government about the existence of deviation by civilservants that need to be transferred. It is recommended that the process and procedure of the PNS mutationshould be done transparently, openly and based on mapping the needs of employees by SKPD or at therequest of SKPD and not because of other factors beyond that. A strategic partner organization that isneutral for local government to oversee the process of employee reform is necessary to prevent the KKNpractices in the process.Keywords: Transparency, Employee Mutation